2018
DOI: 10.1111/jon.12580
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure Correlates with Memory Performance in Healthy Children: A Diffusion Tensor Imaging Study

Abstract: BACKGROUND AND PURPOSE The complex function of memory has been linked to both brain gray and white matter (WM). WM abnormalities are associated with memory impairment in pathological conditions. We investigated whether variation in WM microstructure in healthy children also correlates with memory performance. METHODS Sixty‐five 7.5 to 8.5‐year‐old healthy children had a brain MRI scan using diffusion tensor imaging (DTI). They were also assessed for memory performance using the Children's Memory Scale (CMS). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(81 reference statements)
0
6
0
1
Order By: Relevance
“…The question that arises from this is whether the planatory power of interindividual differences in the cortical microstructure alone is sufficient to account for performance differences in specific cognitive abilities in this po ulation or whether the lack of findings in the present analysis may instead rather caused by an inadequately chosen method. Indices of white matter microstructure ha previously been found to explain cognitive performance differences in typically develo ing children [69][70][71]. In view of this, it does not seem far fetched to expect a similar patte with respect to cortical microstructure.…”
Section: Discussionmentioning
confidence: 88%
“…The question that arises from this is whether the planatory power of interindividual differences in the cortical microstructure alone is sufficient to account for performance differences in specific cognitive abilities in this po ulation or whether the lack of findings in the present analysis may instead rather caused by an inadequately chosen method. Indices of white matter microstructure ha previously been found to explain cognitive performance differences in typically develo ing children [69][70][71]. In view of this, it does not seem far fetched to expect a similar patte with respect to cortical microstructure.…”
Section: Discussionmentioning
confidence: 88%
“…In all analyses GA at birth, postmenstrual age at time of MRI, birth weight Z-score and days of ventilation will be entered as covariates. These analyses have been used in several other observational and intervention studies conducted in the UMC Utrecht and other research groups, in preterm infants at TEA (mean and median GA of 28.7 weeks), [52,64] healthy and asphyxiated full term infants, [65,66] as well as children at school age (7.5-8.5 years and 12 years of age) [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found evidence for abnormalities in white matter connectivity in autism and other IDDs [107,108], although these findings are not universal [109]. Even in typically developing adolescence, there appears to be a relationship between white matter structures and cognitive abilities [110]. Intriguingly, sleep variability in adolescence has been associated with alterations in brain connectivity, reduced academic performance and increased risk-taking behaviour [111][112][113].…”
Section: Poor Sleep In Adolescents With Intellectual and Developmentamentioning
confidence: 99%